Transcultural Dilemma and Identity Crises in Jhumpa Lahiri’s Interpreter of Maladies - Rahman, Muhd. Mustafizur (Integrated Journal for Research in Arts and Humanities, 2023)
These nine cohesive stories Lahiri has written, most of which are set around in India, and the United States, the United Kingdom, etc. are much regarded. These immigrants typically experience hallucinations or seek for their own distinctiveness. Like its majority of these works are set in both India and the United States, they highlight the problem of Indo-American culture and identity. Its majority of her paintings depict three descendants of immigrants into America, mostly from the Indian Bengali community, who are struggling with questions of their ethnic identity. Inside the majority in these tales, the protagonists were engaged with their profession, and they have shown genuine compassion towards her as they search out their individuality. This same majority of first immigrants in her writings experience ethnic crises despite their greatest efforts to maintain their ideas, morals, as well as other lifestyles; yet, many struggle with identification conflicts as a result of living in exile. An essay would mainly discuss Jhumpa Lahiri's writings' identification crises, with "Interpreter of Maladies" receiving particular attention.